The Effect Of Combining Different Natural Feeds On Growth And Survival Rate Of Maanvis Larvae (Pterophyllum sp) - Rais, Muhammad; Sukendi, Sukendi; Nuraini, Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT     The research was conducted from 7 december 2017 until 5 january 2018 in the fish hatchery and breeding laboratory faculty of fisheries and marine university of Riau. The aim of research was to evaluate the effect of combination of natural feed on the growth and survival rate of maanvis larvae. The method used in this research was the experimental method using a complete randomized design (CAD) with one factor with three treatment and three replications. The best growth rate was obtained at the treatment T2 (Daphnia sp 10 D + Culex sp 10 D + Tubifex sp10 D) with larvae growth of 0,73 g Bw, with 2,7 cm total length, 14,35%/d growth of daily weight rate, and survival rate of 95,56 %. The water quality parameters during the research were temperature 27,2-28,7 0C, pH 6,5-7,4, DO 4,3-6,0 ppm. Keyword : Pterophyllum sp, combination, growth, and survival rate